(3MGTjI efdG RGOg Ydi GdMGTjI GdYUGejI Ydi TQM oedG LGejs - (3eMeO GdcQOj GdSgQhGfj GdTgjQ H` efdG RGOgs; (3GdYUGe GdGSaQGjjfj , YUGe GdOjf EHQGgje Hf eMeO Hf YQH TGg GdESaQGjjfj, GdYUGe GdESaQGjjfj,J (B945 (3g` s ((3eUWai Hf eMeO GdTQGHj s)
(3ChdgG (B:s
(3hHYO, jbhd eMeO GdcQOj GdSgQhGfj, GdTgjQ HefdG RGOg gPg MhGT aGFbI s
(3BNQgG (B:s
(3Ke GdeQLh efge Ef hLOhG ajgG TjFkG ef GdNdd Cf jYPQhfj aj Pdc eY eG Hj ef GdcdGd hGdedGd hbO JeJ GdMGTjI s
(3Vef eLehY s
(3TQM edG LGejs
(3TQM GdcGajI dGHf GdMGLH fhQGdOjf YHOGdQMef Hf CMeO GdLGej GdeJhai (B898(3g``s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs